« Du ras des pâquerettes textuelles... à la lutte des classes » : entretien avec Jean-Jacques Lecercle autour de Raymond Williams, du matérialisme culturel et des cultural studies - Jean-Jacques Lecercle (Contextes)
This interview focuses on Jean-Jacques Lecercle’s decisive encounter with Raymond Williams’s work. It looks at Williams’s biography, explores the major approaches and concepts he developed (linguistic and textual analysis, “dominant / residual / emergent”, structure of feeling, etc.), and highlights their crucial contribution to the Marxist philosophy of language, to literary analysis (from Jane Austen to contemporary postcolonial literature), and to the field of literary studies at large. The interview also discusses the limits and extensions of Williams’s work by connecting it with other thinkers related to Marxism and cultural studies.